2002
DOI: 10.1097/00003226-200205000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Management of Postoperative Bullous Keratopathy With Nonpreserved Human Amniotic Membrane

Abstract: NP-AMT is a good alternative for the management of painful PBK in eyes with poor visual potential; NP-AMT is widely available, the technique is easy to perform, and it has good results from both the symptomatic and esthetic standpoint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 37 publications
3
39
1
4
Order By: Relevance
“…Defects in the corneal epithelium requiring surgical reconstruction may result, for example, from ulcers [1][2][3][4][5][6][7] , bullous [8,9] or band [10] keratopathy, and thermal and chemical burns [11,12] . Large defects in the conjunctiva carry the risk of scarring that can disfi gure the conjunctiva and even restrict ocular motility.…”
Section: Introductionmentioning
confidence: 99%
“…Defects in the corneal epithelium requiring surgical reconstruction may result, for example, from ulcers [1][2][3][4][5][6][7] , bullous [8,9] or band [10] keratopathy, and thermal and chemical burns [11,12] . Large defects in the conjunctiva carry the risk of scarring that can disfi gure the conjunctiva and even restrict ocular motility.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms of PBK resolved completely in 8 (88%) patients and partially in 1 patient. 18 Anterior stromal puncture involves multiple micro punctures. The subsequent healing response leads to alteration of extracellular matrix by increasing the expression of fibronectin, laminin and collagen IV at the puncture sites.…”
Section: Discussionmentioning
confidence: 99%
“…Dual et al (2004) and Mejia et al (2002) reported that both preserved and non-preserved amniotic membrane can be stored. Dimethyl sulfoxide (DMSO) has been used as an alternative to the preservation of amniotic membrane by replacing the rinsing with saline and antibiotics; AzuaraBlanco et al (1999) used DMSO to 4, 8 and 10, while Kubo et al (2001) used the same product to 0.5, 1.0 and 1.5 M for the washing membrane.…”
Section: Preparation and Preservationmentioning
confidence: 99%
“…Dimethyl sulfoxide (DMSO) has been used as an alternative to the preservation of amniotic membrane by replacing the rinsing with saline and antibiotics; AzuaraBlanco et al (1999) used DMSO to 4, 8 and 10, while Kubo et al (2001) used the same product to 0.5, 1.0 and 1.5 M for the washing membrane. After such treatment, it may be stored in 1.5 M DMSO to −80˚C for several months [11,19,26,54].…”
Section: Preparation and Preservationmentioning
confidence: 99%